THE DIRECT APPROACH OF GENERAL DYNAMIC OPTIMAL CONTROL: NONLINEAR PROGRAMMING AND RUNGE-KUTTA METHOD - Boonpratatong, Amaraporn; Veeraklaew, Tawiwat (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2004)
-